PROBLEM SOLVING: INTRODUCTION OF SCIENCE LEARNING IN ELEMENTARY SCHOOL - Fatchul Fauzi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
As a high-level thinking ability, problem solving is developed at the level of primary school education, especially in the high grande. Problem solving is the concept of thinking ability by understanding the problems presented and using the right solutions with various kinds of strategy development. The purpose of this study is to analyze the problem solving of students through the results of student worksheets on green plant material. The results show that students' problem solving language is simply with a problem solving indicator framework, including: building knowledge related to issues / problems, determining keywords, determining solution strategies, and determining conclusions.